Implementation of full carbon-based three-dimensional interconnects - Zhu, Ye (Nanyang Technological University, 2020)
Attributing to its outstanding electrical properties and compatibility with modern electronic devices, there have been numerous studies reported on the fabrication and characterization of carbon nanotube (CNT)-graphene heterostructure. Although there have been some efforts toward the application of CNT-graphene heterostructure for interconnects, none of them demonstrated a full carbon-based implementation in the through silicon vias (TSVs) for three-dimensional integrated circuits (3-D ICs). In this study, the development and optimization of CNT-graphene heterostructure for its application in TSV interconnects were reported. Carbon nanotubes (CNTs) were firstly free-standing grown on the graphene with thermal chemical vapor deposition (TCVD) technique, yielding sufficient length (~334μm) and density (estimated as ~1011 cm-2) which fulfilled the TSV application requirement. Subsequently, the growth of CNTs within TSVs on the bottom graphene electrodes was successfully demonstrated. The fabrication processes of top wafer with TSVs of various diameters (5-50μm) and bottom wafer with patterned graphene electrodes and catalyst deposition were successfully developed. Next, top TSV wafer and bottom graphene wafer were bonded and manually ground, followed by wet and dry etching to completely remove the handling wafer and buried oxide to expose the underlying TSV holes. By using the same TCVD technique, successful growth of CNTs within the fabricated TSVs on top of the graphene electrodes was achieved. In order to complete the full-carbon 3-D interconnection, assembly process of top graphene layer after CNT growth needs to be further explored. In this work, transfer process of a top graphene layer onto the as-grown CNT bundles was successfully performed with direct graphene-to-CNT contact at the interface. The electrical properties of CNT/graphene contact were characterized by four-point-probe (4PP) I-V measurements of the graphene bridge structure. The results suggested that an ohmic contact was achieved between the graphene and CNTs. Low CNT bump resistance of 2.1Ω for 90,000 µm2 CNT area including the CNT/graphene contact resistance was obtained, demonstrating reduction of contact resistance between CNT and Au under the same fabrication and measurement conditions. The conditions of femtosecond laser annealing for the fusion of graphene and CNTs were explored in this work as well. After the laser power tuning, 0.0166W was selected as the optimized value for annealing. Laser line scanning was applied at the graphene/CNT interface and the electrical properties of the pristine graphene bridge and annealed graphene bridge samples were characterized. The total resistance of the bridge structure dropped to its lowest (27.3 Ω) after the first laser scanning and increased after the second and third laser annealing. However, the obtained outcomes give insufficient evidences to conclude that the resistance dropping was due to the fusion of graphene and CNTs by the laser annealing. Further studies are needed to verify the formation of CNT-graphene bonding and its impact on the overall resistance upon laser annealing.